EFFICIENCY OF TRADITIONAL METHODS VERSUS INNOVATIVE METHODS IN LEARNING SPANISH - Alina-Viorela PRELIPCEAN (Association of Social and Educational Innovation, 2023)
The present article proposes a detailed analysis of the efficiency of traditional and innovative methods in learning the Spanish language. The impact of different approaches on language comprehension and retention is explored by examining recent research in pedagogy and linguistics.             In the continuous evolution of technology and education, it is crucial to evaluate the effectiveness of methods used in teaching a foreign language. This study focuses on the Spanish language, analyzing traditional teaching methods compared to innovative approaches. Following the conducted study, comparing the results obtained through traditional methods with those of innovative methodology, the article highlights the advantages and disadvantages of each of them. Aspects related to student motivation and performance are discussed.             Our study suggests that a balanced combination of traditional and innovative methods could be most effective in promoting the learning of the Spanish language. Adaptability to the individual needs of students and the integration of modern technologies are essential to maximize the effectiveness of the teaching process.